Aggregation of ice-nucleating macromolecules from Betula pendula pollen determines ice nucleation efficiency - F. Wieland; F. Wieland; N. Bothen; R. Schwidetzky; T. M. Seifried; T. M. Seifried; P. Bieber; P. Bieber; U. Pöschl; K. Meister; K. Meister; M. Bonn; et al. (Biogeosciences)
Various aerosols, including mineral dust, soot, and biological particles, can act as ice nuclei, initiating the freezing of supercooled cloud droplets. Cloud droplet freezing significantly impacts cloud properties and, consequently, weather and climate. Some biological ice nuclei exhibit exceptionally high nucleation temperatures close to 0 °C. Ice-nucleating macromolecules (INMs) found on pollen are typically not considered among the most active ice nuclei. Still, they can be highly abundant, especially for species such as Betula pendula, a widespread birch tree species in the boreal forest. Recent studies have shown that certain tree-derived INMs exhibit ice nucleation activity above −10 °C, suggesting they could play a more significant role in atmospheric processes than previously understood. Our study reveals that three distinct INM classes active at −8.7, −15.7, and −17.4 °C are present in B. pendula. Freeze drying and freeze–thaw cycles noticeably alter their ice nucleation capability, and the results of heat treatment, size, and chemical analysis indicate that INM classes correspond to size-varying aggregates, with larger aggregates nucleating ice at higher temperatures, in agreement with previous studies on fungal and bacterial ice nucleators. Our findings suggest that B. pendula INMs are potentially important for atmospheric ice nucleation because of their high prevalence and nucleation temperatures.